(3aj eMGSHI GdJcGdja dCZQGV bjGS JcdaI GdEfJGLs - (3YHO GdMj(B, (3eQYjs ((3GdEScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 1998)
(3aj eGgjI GdJcdaI heVehfgG hCZQGV hCSS bjGSgG ,eGgjI GdJcdaI ,CZQGV hCSS bjGS GdJcdaI,WHjYI GdUfGYI hYfGUQ JcdaI GdGfJGL,CfXeI JcGdja GGdeQGMd,JNUjU GdJcdaI GdeTJQcI aj GdefJLGJ GdeJUdI hGdaQYjIs
Keywords: (3GdGfJGLs; (3eMGSHI GdJcGdjas